Ultrawide photoresponse in ZnO/ZnSe coaxial nanowires with a threshold of 0.8 eV. (14th September 2015) - Wang, Weiping; Cao, Yiyan; Wu, Zhiming; He, Jialun; Luo, Qiang; Bhutto, Waseem Ahmed; Li, Heng; Wen, Yuhua; Li, Jing; Li, Shuping; Kang, Junyong
Abstract Nanostructured wide-bandgap semiconductors have great potential for photocatalytic applications because of their high stability and photocatalytic ability in aqueous solution. However, these materials are poor absorbers of photons in the solar spectrum and yield modest conversion efficiencies. This work demonstrates that photoresponse can be widely extended by strain-induced modification in ZnO/ZnSe coaxial nanowires. An ultrawide photoresponse was theoretically predicted with threshold ranging from 0.4 eV to 1.8 eV in ultrathin nanowires because of the large core strain. The lowest photoresponse threshold of 0.82 eV was observed in the experiment, which almost covered up to 94% of solar power. This result suggested that an unusually high utilization ratio of solar light was achieved. This work provided a strategy to design and develop a stable and efficient photocatalyst based on wide-bandgap semiconductors.